Traditional Malay Zapin Creation Dance Activities to Stimulate the Gross Motor Skills Development of Children Aged 5-6 Years - Suriana, Suriana; Miranda, Dian; Amalia, Annisa (International Journal of Learning and Instruction (IJLI), 2024)
This study aims to describe the dance activities of traditional Malay zapin creations to stimulate the development of gross motoric skills of children aged 5-6 years. The research method used is descriptive, qualitative form. The subjects in this study were two B class teachers and 32 B class children. Data collection techniques used are observation, interviews, and documentation. Dancing is an interesting activity for children and can develop children's gross motoric skills in a fun way. The development of motor skills is a very important factor in the overall development of children. Motoric development in children develops in line with the maturity of the child's nerves and muscles. The results showed that traditional Malay zapin dance creations stimulate gross motoric development of children aged 5-6 years with coordinated body movements, coordination of eye, head, hand and leg movements, as well as coordination of right and left-hand movements, from this aspect children can already imitate good movements according to what is taught and directed by the teacher.  Keywords: Dancing Activities, Gross Motoric, Early Childhood